2019
DOI: 10.1021/acs.energyfuels.9b01046
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Methane Hydrate in Oil–Water Emulsion Governed by the Hydrophilic and Hydrophobic Properties of Non-Ionic Surfactants

Abstract: As oil and gas production moves into deep water, the formation of gas hydrate has been a primary flow assurance challenge in the deep water pipelines. Because of the complex composition of crude oil and various additives, the objective of this work is to study the effect of additive hydrophilic–hydrophobic property on hydrate formation in the emulsion, which usually occurs in pipelines. The formation experiments of methane hydrate in emulsion with the same water cut but surfactants of different hydrophilic lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 42 publications
0
15
0
1
Order By: Relevance
“…Therefore, hydrate film growth is significantly affected by heat transfer at the gas−water interface. 112,113 Considering the complex composition of crude oil and various additives in real pipelines, Liu et al 114 studied the effect of the hydrophilicity and hydrophobicity of the additives on hydrate formation in the oil and water emulsion. When the hydrophilic lipophilic balance (HLB) value of the surfactant ranged between 8 and 10, the hydrate growth process was promoted in the phase transition region due to a smaller interfacial tension between the water and the oil.…”
Section: Ngh Phase Equilibria and Kinetics Research In Chinamentioning
confidence: 99%
“…Therefore, hydrate film growth is significantly affected by heat transfer at the gas−water interface. 112,113 Considering the complex composition of crude oil and various additives in real pipelines, Liu et al 114 studied the effect of the hydrophilicity and hydrophobicity of the additives on hydrate formation in the oil and water emulsion. When the hydrophilic lipophilic balance (HLB) value of the surfactant ranged between 8 and 10, the hydrate growth process was promoted in the phase transition region due to a smaller interfacial tension between the water and the oil.…”
Section: Ngh Phase Equilibria and Kinetics Research In Chinamentioning
confidence: 99%
“…Stirring promotes the mixing of incompatible gas and liquid, and it rapidly renews the reaction interface, thereby enhancing the transfer of heat and mass. Continuous stirring simultaneously increases material diffusion, accelerates material dissolution in the liquid phase, shortens the induction period, and increases the rate of hydrate formation [41,42]. Golombok et al [43] suggested that hydrate formation is limited by insufficient gas-liquid mixing.…”
Section: Characteristics Of Hydrate Formationmentioning
confidence: 99%
“…The rheological of properties of the hydrate slurry were rarely mentioned. The appearance of hydrate may make the slurry difficult to flow and may cause unpredictable pipeline blockage. , The rheological property of a hydrate slurry are critical to evaluate the flow performance of the hydrate slurry and the risk of blockage in hydrate solid fluidization and the pipeline transportation process. , …”
Section: Introductionmentioning
confidence: 99%